Influence of yttrium doping on the structural, morphological and optical properties of nanostructured ZnO thin films grown by spray pyrolysis. Issue 6 (15th April 2019) - Bazta, O.; Urbieta, A.; Piqueras, J.; Fernández, P.; Addou, M.; Calvino, J.J.; Hungría, A.B.
Abstract: This study reports on the deposition of highly transparent, n-type ZnO thin films on glass substrate at 450 °C using spray pyrolysis processing, with the simultaneous insertion of yttrium (Y) at different percentages (0, 2, 5, 7 at%) as a dopant. The effect of Y doping on the structure, morphology and optical properties of Y doped ZnO (ZnO:Y) was investigated for optoelectronic applications. The obtained thin films were characterized by means of X-ray diffraction, field-emission scanning electron microscopy (FESEM), UV–visible absorbance measurements, photoluminescence (PL) and cathodoluminescence (CL) spectroscopy. The as-prepared films exhibit well-defined hexagonal wurtzite structure grown along [002]. Field emission scanning electron microscope micrographs of the pure ZnO and ZnO:Y showed that the films acquired a dominance of hexagonal-like grains, the morphology was influenced by Y incorporation. All the films showed high transparency in the visible domain with an average transmittance of 83%. The band gap energy, Eg, increased from 3.12 eV to 3.18 eV by increasing the Y doping concentration up to 5 at% and then decreased to 3.15 eV for 7 at% Y content. The PL and CL measurements reveal a strong ultraviolet (UV) emission, suggesting that the as-prepared ZnO:Y thin films can potentially be used in optoelectronic devices.